Castration-Resistant Prostate Cancer: Mechanisms, Targets, and Treatment. (5th March 2012) - Amaral, Teresa Maria Santos; Macedo, Daniela; Fernandes, Isabel; Costa, Luis
Abstract : Patients with castration-resistant prostate cancer (CRPC), who progress after docetaxel therapy, had until very recently, only a few therapeutic options. Recent advances in this field brought about new perspectives in the treatment of this disease. Molecular, basic, and translational research has given us a better understanding on the mechanisms of CRPC. This great investment has turned into a more rational approach to the development of new drugs. Some of the new treatments are already available to our patients outside clinical trials and may include inhibitors of androgen biosynthesis; new chemotherapy agents; bone-targeted therapy; and immunotherapy. This paper aims to review the mechanisms of prostate cancer resistance, possible therapeutic targets, as well as new options to treat CRPC.